2014
DOI: 10.1007/s12070-014-0705-7
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Support for Fascia Graft in Type I Tympanoplasty

Abstract: To evaluate the success rate, in terms of anatomical and functional results, in our technique of cartilage support for fascia graft in type I tympanoplasty. Retrospective study of tragal cartilage support for fascia graft in tympanoplasty for large central perforation in 748 patients was carried at an academic institution during January 2004 to March 2012. Patients' age ranged from 11 to 65 years. 325 (43.4 %) male and 423 (56.6 %) female patients were operated and mean post-operative follow up was of 24 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…In a similar technique, Mundra et al 21 . and Kulkarni et al 5 . reported anatomical success (perforation closure) rates of 95.74 per cent and 98.3 per cent respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a similar technique, Mundra et al 21 . and Kulkarni et al 5 . reported anatomical success (perforation closure) rates of 95.74 per cent and 98.3 per cent respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Since the introduction of tympanoplasty by Wullstein in 1952, 2 and Zollner in 1955, 3 different types of graft materials have been used for the repair. As a result of ease of accessibility at the surgical site, abundant availability, low basal metabolic rate and similar thickness to the tympanic membrane, temporalis fascia grafts have been extensively used worldwide, with successful closure of tympanic membrane defects in over 90 per cent of normally ventilated middle ears 4 , 5 . However, temporalis fascia has much poorer healing in cases of tubal dysfunction, an adhesive process, tympanic fibrosis and total perforation, and in revision surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 However, the routine use of CST in all cases is still controversial. In a study by Kulkarni et al, 15 all patients who underwent type 1 tympanoplasty, had an additional support of cartilage anteriorly, medial to annulus. The limitation in the study was that mean follow-up in our patient group is 9 months.…”
mentioning
confidence: 99%
“…Kulkarni et al also observed males as 43.4% and females 56.6% in their study. 10 Khan et al also found males 57.85% and females 42.15% in their study. 11 Kyrodimos et al found males 50% and females 50%, Boone males 55.79% and females 44.21%.…”
Section: Discussionmentioning
confidence: 54%